Effect of lipid inclusion levels in aquafeed on carcass composition, quality change during storage and nutrient excretion in dusky kob (Argyrosomus japonicus) - Ginindza, Nhlanhla Joseph (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2016)
Dusky kob, Argyrosomus japonicus, is an aquaculture species in South Africa that is in pilot commercial production. While the major nutrient requirements of the species are known, the advantages of incorporating formulated feeds into the diet of the species has yet to be fully explored. Research on formulated feed composition is required to: minimise input costs; improve the organoleptic properties and meat quality; and minimise nutrient loss, which contributes to environmental pollution. This study sought to test the impact of different lipid levels in aquafeeds fed to dusky kob juveniles by determining: (i) growth performance, feeding efficiency, proximate and fatty acid composition; (ii) chemical changes and shelf-life of refrigerated fish fillets; and (iii) metabolic rates and nitrogen excretion of juvenile dusky kob. And more...
Keywords: Aquaculture